Randomized Clinical Trial of the Effectiveness of a Home-Based Advanced Practice Psychiatric Nurse Intervention: Outcomes for Individuals with Serious Mental Illness and HIV - Nancy P. Hanrahan; Evan Wu; Deena Kelly; Linda H. Aiken; Michael B. Blank (Nursing Research and Practice)
Individuals with serious mental illness have greater risk for contracting HIV, multiple morbidities, and die 25 years younger than the general population. This high need and high cost subgroup face unique barriers to accessing required health care in the current health care system. The effectiveness of an advanced practice nurse model of care management was assessed in a four-year random controlled trial. Results are reported in this paper. In a four-year random controlled trial, a total of 238 community-dwelling individuals with HIV and serious mental illness (SMI) were randomly assigned to an intervention group (n=128) or to a control group (n=110). Over 12 months, the intervention group received care management from advanced practice psychiatric nurse, and the control group received usual care. The intervention group showed significant improvement in depression (P=.012) and the physical component of health-related quality of life (P=.03) from baseline to 12 months. The advanced practice psychiatric nurse intervention is a model of care that holds promise for a higher quality of care and outcomes for this vulnerable population.